Embedding environment consciousness in English Language Teaching (ELT): Challenges and prospects for sustainable learning - Fadila Vani Dea Risanti; Muhammad Zanuar Irsyad (Penelitian Ilmu Pengetahuan Sosial, 2026)
Background: Integrating environmental awareness into English Language Teaching (ELT) has become increasingly important as a response to global sustainability challenges and the need to cultivate environmentally responsible learners through language education. Methods: This study employed a descriptive qualitative approach using an integrative literature review of secondary data derived from internationally indexed scientific publications, national journal articles, and relevant policy documents. The analysis was conducted through source selection, thematic categorization focusing on challenges, strategies, and future prospects, and cross-literature integration. Findings: The results reveal several barriers to integrating environmental awareness into ELT, including limited environmental literacy among teachers, insufficient eco-pedagogical training, and curricula that remain predominantly language-oriented. However, innovative approaches such as project-based learning, Content and Language Integrated Learning (CLIL), and the integration of green digital literacy have demonstrated considerable potential in engaging students with environmental issues while simultaneously enhancing language competencies. The findings further indicate that ELT can serve as an effective platform for promoting sustainability values and ecological responsibility. Conclusion: Embedding environmental awareness into ELT is essential for advancing the goals of Education for Sustainable Development (ESD), enabling the development of critical, environmentally conscious, and globally responsible learners capable of contributing to sustainable futures. Novelty/Originality of this article: This study offers a comprehensive synthesis of challenges, strategies, and future directions for integrating environmental awareness into ELT, contributing to the advancement of eco-pedagogical discourse while providing practical implications for curriculum development and teacher professional training oriented toward sustainability.